The Effect of a Mentoring Program on Competition Orientation for Football School Athletes - Sarmad Abdul Ridha Abdul Hussain Al Hussaini 1, Mohamed Abdel-Reda2 , Khaled Mohamed Reda3, Haider N (Indian Journal of Forensic Medicine & Toxicology, 2020)
The research problem was centered in the fact that despite all the efforts made by the training staff toassist the players in raising their technical level, the researchers with their personal experience because theyworked in the field of arbitration and arbitrated many of the matches that took place for the players of thespecialized school in the province of Babel note that there are some players They do not carry a positiveattitude towards competition and this is enough to affect the level of their performance, and therefore theyare born with weakness in perseverance and dedication to sports competition, and this leads to a low level ofperformance due to the lack of a positive orientation of the players towards competition, which is reflected onhis performance Inside the stadium, so the researchers adapted to study this problem by knowing the realityof the competitive orientation of the players and building an indicative program with special exercises toraise the level of their competitive orientation in football. The researchers used the realistic treatment methodas one of the psychological methods to improve these variables because it deals with them realistically, andthe objectives of the research were to build an indicative program With special exercises for the players ofthe specialized school in the province of Babylon, football, to identify the effectiveness of the pilot programwith special exercises in the orientation towards competition among the players in the province of Babylonfootball, the researchers used the experimental method in the complex method And the two controlling andexperimental equivalents with pre and post-test for their suitability to the nature of the research problem onthe players of specialized schools in the middle Euphrates football who are under (17) years old and whosetotal number is (175) players, The researchers concluded that there is an effect of the pilot program with itsexercises In flat lift The competitive orientation of football with the experimental group, and real differencesemerged in the level of competition orientation between the control and experimental research groups andin favor of the experimental group, and the use of realistic guidance commensurate with raising the level ofcompetition towards the players of the experimental group in the specialized school of football.